Stress and Coping Among Family Caregivers of Patients With a Destination Therapy Left Ventricular Assist Device: A Multicenter Mixed Methods Study. (October 2021) - McIlvennan, Colleen K.; Jones, Jacqueline; Makic, Marybeth; Meek, Paula M.; Chaussee, Erin; Thompson, Jocelyn S.; Matlock, Daniel D.; Allen, Larry A.
Abstract : Background: Family caregivers of patients with a destination therapy left ventricular assist device play a central and formalized role in postimplant care. We aimed to characterize longitudinal stress, predictors and correlates of stress, and coping processes among left ventricular assist device caregivers. Methods: We performed a sequential, exploratory, mixed-methods study from 6 diverse left ventricular assist device programs. The primary outcome for the quantitative analysis was the Perceived Stress Scale-10 at 6 months (0–40). Based on the quantitative findings and guided by the Transactional Model of Stress and Coping, semistructured interviews explored causes of stress and coping processes. Integration was performed during the qualitative and interpretation phase. Results: A total of 96 caregivers met inclusion criteria for quantitative analysis. Mean (SD) Perceived Stress Scale score was 14.3 (5.5) preimplant and 11.8 (6.9) at 6 months. Preimplant, only decreased preparedness for caregiving was associated with higher Perceived Stress Scale score at 6 months. At 6 months, increased caregiver depressive symptoms, decreased caregiver preparedness for caregiving, and lower patient quality of life were associated with higher Perceived Stress Scale score. Qualitative analysis of 25 caregivers revealed the causes of stress coalesced around 3 themes: (1) lack of preparedness to be a caregiver, (2) uniqueness of stress for the caregiver and patient situation, and (3) caregiving responsibilities physically and emotionally impacting caregivers. To cope with stress, most caregivers employed emotion-focused coping. Conclusions: In family caregivers of patients with a left ventricular assist device, higher perceived stress was associated with lower caregiver preparedness, higher caregiver depressive symptoms, and lower patient quality of life. Emotion-focused coping strategies were common for caregivers. Future work should better prepare caregivers for this role and support them through the caregiving experience. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02344576. Abstract : Supplemental Digital Content is available in the text.